Trade-offs and Synergies of Soil Restoration Through Conservation Tillage: Strategies for Sustainable Agri-Food Systems in Riverine Agroecosystems - S. Pazhanisamy; Rodda Chandana Devi; Sunita Kumari Meena; E. Rathinaguru; R. Sushma Devi; S. Mala; Dinesh Jinger; Raj Kumar Jat; H. S. Jat; Vijay Singh Meena; M. L. Jat (Anthropocene Science, 2026)

Assessment of Carbon and Phosphorus Stoichiometry in Different Land use Systems as a Tool for Future Planning in Agroecosystems in North Central India - Ram Swaroop Meena; Kundan Kumar Singh; Gourisankar Pradhan; Suchismita Satapathy; Sanjeev Kumar; Krishan Kant Mina; Sandeep Kumar; Cherukumalli Srinivasa Rao; Rattan Lal (Anthropocene Science, 2026)

Unfolding Food Access in a Predominantly Rural Landscape: Geospatial Insights into Habitat Segments and Food Linkages - Amit Kumar Srivastava; Tanu Kumari; Prakashan Chellattan Veettil; Kranthi Kumar Challa; Pavan Kumar Yeggina; Afrin Zainab (Anthropocene Science, 2026)

Evaluating Meteorological Signatures of Forest Fire Events Across Diverse Regions of India - R. Bhatla; Shishank Prakash; Richa Singh (Anthropocene Science, 2026)

Machine Learning-Based Above-Ground Biomass Prediction in Indo-Myanmar Biodiversity Hotspot of India, Using Google Earth Engine - Kangujam Premkumar; Vivek Vaishnav; Sanjay Singh; Gopal Shukla (Anthropocene Science, 2026)

Toward Resilient Landscapes: Unpacking India's Land Degradation Challenges, Restoration Policies, and Future Directions - Sayalee Avinash Gulhane; Shalini Dhyani (Anthropocene Science, 2026)

Doomsday Clocks in the Anthropocene Era: Understanding Existential Risks To Humanity - Sudhanshu Kumar; Gopal Shankar Singh (Anthropocene Science, 2025)

Stubble Burning and Air Pollution in Delhi: Assessment of Mitigation Strategies - Manas Kumar Jha; Ruchi Gupta; Ashutosh Kainthola; Vaishali Sahu; Pranavi Mishra; Dilip Kumar Markandey; Shahbaz Alam (Anthropocene Science, 2025)

A Call for the Scientific Community to Adopt Environmental, Social and Governance Principles - Jurjen J. Luykx; Elisabetta Burchi (Anthropocene Science, 2025)

Climate Resilient Crop Varieties: Mainstreaming to Improve Yield and Moderate Farmers’ Risk - D. K. Yadava; Ranjay K. Singh; V. B. Patel; T. R. Sharma; S. K. Singh; Sudhakar Pandey; P. R. Choudhury; Firoz Hossain; R. R. Burman; U. S. Gautam; Himanshu Pathak (Anthropocene Science, 2025)

Assessing the Feasibility of Productive Weed Use: A Decision Support Framework for Land Stakeholders - James P. Westfield; Elizabeth M. Wandrag; Lindsay C. Stringer (Anthropocene Science, 2025)

Emerging Pollutants in the River Ganga and its Tributaries – Current Status, Future Impacts and Fate of Riverine Ecosystems - Divya Dubey; Venkatesh Dutta (Anthropocene Science, 2025)

Correction: Integration of Machine Learning into Geospatial Modelling for Forest Fire Risk Assessment in Hamirpur District, Himachal Pradesh (India) - Prachismita Nayak; Shruti Kanga; Suraj Kumar Singh; Gowhar Meraj; Pankaj Kumar; Saurabh Kumar Gupta; Bhartendu Sajan (Anthropocene Science, 2025)

From Pixels to Molecules: Innovative Strategies for Invasive Alien Plant Species Monitoring and Management - L. H. Namitha; Shalini Mudalkar; C. Sudhakar Reddy (Anthropocene Science, 2025)

Application of City Biodiversity Index to the Fast-Expanding City of Delhi, India, for Urban Sustainability and Resilience - Chandan Das; Satish Chandra Garkoti; Shalini Dhyani (Anthropocene Science, 2025)

City Biodiversity Index Assessment for Data-Driven Blue–Green Infrastructure Planning for Urban Sprawls: Lessons from Nagpur, India - Manu Thomas; Anuj Kumar Tripathi; Athira Prakash; Shalini Dhyani (Anthropocene Science, 2025)

A Comparative Analysis of Emissions from Mining Sector in G20 Countries - Aakash Kumar; Abhishek Kumar; Vatsala; Sanjay Singh (Anthropocene Science, 2025)

Impact of Climate Change-Mediated Tragedies: An Account of Extreme Rainfall Event in Rio Grande do Sul, Brazil - Daniela Debone; Ronan Adler Tavella; Arnaldo Lopes Colombo; Ana Cristina Gales; Flávio Manoel Rodrigues da Silva Júnior; Simone Georges El Khouri Miraglia (Anthropocene Science, 2025)

Anthropogenic Footprint on Island Ecosystems: Quantifying Declining Ecosystem Services in Mauritius - Jay Rovisham Singh Doorga (Anthropocene Science, 2025)

Break the Political Deadlock on Drought Through an Integrated Policy Approach - Lindsay C. Stringer; Johannes Kruse; Mariam Akhtar-Schuster; Rodrigo Andrade Ramirez (Anthropocene Science, 2025)

Assessment of Millets Awareness, Cultivation, and Consumption Pattern in Northwestern Himalaya: A Case Study from Jammu and Kashmir, India - Shweta Sharma; Usha Mina; Chubbamenla Jamir; Meenakshi Gupta (Anthropocene Science, 2025)

Human Relations with Wildlife, Forests, and Rivers Defining Ribeirinho’s and Extractivist Identities in the Amazonian Xingu River, Pará, Brazil - Itamir Costa Bernaldino; Valeria dos Santos Moraes-Ornellas (Anthropocene Science, 2025)

Analysis of Species Richness Variability, Spatial Distribution, and Carbon Stock in Okalma Natural Forest Reserve, Sudan - Elmugheira M. I. Mohammed; Emad H. E. Yasin; Budi Mulyana (Anthropocene Science, 2025)

Pearl Millet: A Sustainable Source of Food and Nutrition in the Age of Climate Change - Raneem Ismail Al-Khaleel; Tarasatyavati Chellapilla; Chandra Nayaka Siddaiah (Anthropocene Science, 2025)

What Anthropocene Do We Want? - Miguel da Silva Pinheiro; Pablo José Francisco Pena Rodrigues (Anthropocene Science, 2025)

The Anthropogenic Factor as a Driver of Ecosystem Changes - Jaime Gómez-Márquez (Anthropocene Science, 2025)
Throughout history of life, natural events have shaped ecosystems until the human species began to overwhelmingly conquer and exploit this planet. Humans are profoundly altering ecosystems and the natural course of evolution, posing a serious threat to the future of life on our planet. The term "anthropogenic factor" refers to the influence of human actions and population growth on ecosystem structure and dynamics. In light of this, ecosystems can be classified into two categories: (i) natural ecosystems, which remain unchanged by human intervention, and (ii) intervened ecosystems, which have been influenced by the anthropogenic factors. Intervened ecosystems can be further categorized into three types: human-altered ecosystems, human-engineered ecosystems, and urban ecosystems. There is another category of ecosystems, the disappeared ecosystems, whose disappearance may be due to natural catastrophe or human intervention. The disappearance of an ecosystem is a biological tragedy, but it can also represent a new opportunity for life. For the sustainability of the planet as a source of life and to ensure a future for our species in harmony with nature, we need to achieve a sustainable balance between the development and well-being of all human beings, the population growth, the use of the services provided by ecosystems and the preservation of wild nature.

Rethinking Urban Future: Towards Sustainable Cities and Communities - Varsha Mishra (Anthropocene Science, 2025)

Integration of Machine Learning into Geospatial Modelling for Forest Fire Risk Assessment in Hamirpur District, Himachal Pradesh (India) - Prachismita Nayak; Shruti Kanga; Suraj Kumar Singh; Gowhar Meraj; Pankaj Kumar; Saurabh Kumar Gupta; Bhartendu Sajan (Anthropocene Science, 2025)

The Paradox and Fallacy of Global Carbon Credits: A Theoretical Framework for Strengthening Climate Change Mitigation Strategies - Ben Chester Cheong (Anthropocene Science, 2025)
Carbon credit systems have emerged as a key policy tool in global efforts to mitigate climate change. Under these market-based schemes, entities that reduce greenhouse gas emissions below a specified cap are issued tradable credits that can be sold to entities exceeding their emissions allowances. In theory, this creates financial incentives for emissions reductions and allows reductions to occur where they are most cost-effective. However, this Policy Analysis argues that the increasing reliance on global carbon markets as a climate solution is deeply problematic and paradoxical. Drawing on interdisciplinary perspectives from environmental economics, law, ethics, and political ecology, I explore the problem through a theoretical framework elucidating the inherent limitations and fallacies underpinning carbon credit approaches. I contend that carbon markets (1) fail to produce real, verifiable emissions reductions; (2) exacerbate global inequities and undermine climate justice; (3) distort climate policy by emphasising cost-effectiveness over ecological necessity; and (4) delay the structural economic changes needed to achieve deep decarbonisation. My analysis is supported by a narrative review of the literature, case studies, and empirical evidence. This Policy Analysis concludes by proposing alternative climate mitigation approaches that could help transcend the paradoxes of global carbon credits, including accelerating fossil fuel phaseouts, scaling up public investment in low-carbon infrastructure, advancing climate justice principles, and rethinking carbon accounting frameworks. Article Highlights Carbon credit systems have emerged as a key policy tool for mitigating climate change, but their effectiveness and equity are increasingly being questioned. This Policy Analysis explores the problem through a theoretical framework that elucidates four major paradoxes and limitations of carbon markets. The analysis draws on interdisciplinary perspectives and is supported by a narrative review of the literature, case studies, and empirical evidence. The Policy Analysis proposes alternative climate mitigation approaches that could help transcend the paradoxes of global carbon credits. Developing effective and equitable climate change mitigation policies in the coming decades will require moving beyond the limitations of carbon markets. Graphical Abstract

Landslide Risk Assessment in a Century-Old Tea Plantation Range Following Monsoonal Extremes in the Western Ghats of Kerala, India - K. Amal George; P. S. Sunil; A. U. Anish; K. M. Sreejith; Girish Gopinath; A. A. Mohamed Hatha (Anthropocene Science, 2025)

Emerging Research Trends in River Health Assessment: A Bibliometric Analysis - Amit Kumar Tiwari; Rinku Singh; Sanoj Kumar Patel; Sudhanshu Kumar; Nazuk Bhasin; Anil Barla; Gopal Shankar Singh (Anthropocene Science, 2024)

No Sustainability Without Regeneration: A Manifesto from an Entrepreneurial Viewpoint - Andrea Illy; Paolo Vineis (Anthropocene Science, 2024)

Cropping System Intensification: Implications on Food Security and Environmental Sustainability in India - Devideen Yadav; Subhash Babu; Dinesh Kumar Yadav; Anita Kumawat; Deepak Singh; Ajay Kumar Yadav; Sanjay Singh Rathore; Raghavendra Singh; Neeshu Joshi; Rajendra Kumar Yadav; Anup Das (Anthropocene Science, 2024)

A Viable World in the Anthropocene: Living Together in the Common Home of Planet Earth - Jürgen Scheffran; Eberhard Schürmann; Roland Weber; Tim Newfields (Anthropocene Science, 2024)
As the world's population continues to surge, the earth's ecological limits are being stretched. Some of the major threats to habitability stem from the pursuit of perpetual economic growth, and power struggles among nations, leading to ecological and social destruction and ongoing crises. A shift toward wiser earth management could enhance habitability through collective strategies within a global political framework. Key components include adopting renewable energy, limiting ecological footprints, fostering clean prosperity, and promoting peaceful coexistence among nations. Our survival hinges on embracing cooperative security and transitioning toward a collective approach to governance, redirecting resources from militarization toward protection of the global commons. This necessitates international collaboration and democratic participation across temporal and spatial scales, facilitated by a UN-led framework. We believe science should play a crucial role in developing common strategies for a viable world, contingent upon decision-makers prioritizing global cooperation over narrow short-term self-interest. Scientists and policymakers can work together, creating more viable futures through international cooperation and a move away from violence. Moreover, citizens have an important role to play by changing their lifestyles and supporting measures mentioned in this paper.

The Impact of Renewable Energy, Green Finance, and Carbon Emission on Economic Growth: Perspective from Newly Industrialized Economies - Agyemang Kwasi Sampene; Takyi Kwabena Nsiah; John Wiredu (Anthropocene Science, 2024)

Microbiome Bioprospecting for Sustainable Agrobiome and Circular Bioeconomy - Dhananjaya Pratap Singh (Anthropocene Science, 2024)

Micro- and Nanoplastic Pollution in the Anthropocene: Understanding and Addressing a Global Crisis - Karuna Singh; Kapil Kumar (Anthropocene Science, 2024)

Ecosystem Health Assessment in India for Mainstreaming Global Biodiversity Framework Headline Indicator and Prioritising Conservation Action - Shalini Dhyani; Deepu Sivadas; Rajiv Chaturvedi; Amrita Neelakantan; Sonali Ghosh; Sarala Khaling; Simran Sharma; Dhritiman Das; Rajarshi Dasgupta (Anthropocene Science, 2024)

Soil Carbon Sequestration and Agronomic Productivity as Influenced by the Long-Term Organic and Inorganic Fertilisation Under the Upland Rice–Wheat System in Vertisols of Central India - Ch. Srinivasarao; Sumanta Kundu; D. P. Dubey; Rajiv Dubey; S. Rakesh; Rattan Lal; P. C. Abhilash; J. V. N. S. Prasad; G. Pratibha; Somasundaram Jayaraman; K. Mrunalini; K. A. Gopinath; et al. (Anthropocene Science, 2024)

Afforestation Schemes Are Driven by Urbanisation and Tree Outside Forest: A Case Study of India - Harsh Yadav; Takehiro Sasaki (Anthropocene Science, 2024)

Carbon Stocks of Forests and Tree Plantations Along an Elevational Gradient in the Western Ghats: Does Plant Diversity Impact Forest Carbon Stocks? - B. Mohan Kumar; D. Balasubramanian (Anthropocene Science, 2024)

Effect of Disturbance on Micro-environment, Soil Properties and Microbial Biomass in Subtropical Broadleaved Forests of Meghalaya, India - Humayun Samir Ahmed Barbhuyan; Krishna Upadhaya; Gunjana Chaudhury; Aabid Hussain Mir (Anthropocene Science, 2024)

Transitional Contexts and Transformational Pathways Through the Utilisation of Marine Fishery Advisories in Odisha, India: Challenges and Way Forward - Sudip Kumar Kundu; Harini Santhanam (Anthropocene Science, 2024)

Soil Properties and Stoichiometry as Influenced by Land Use, Enclosures and Seasonality in a Semi-arid Dryland in Kenya - Oliver V. Wasonga; Kevin Z. Mganga; Robinson K. Ngugi; Moses M. Nyangito; Dickson M. Nyariki (Anthropocene Science, 2024)
Agropastoralism and nomadic pastoralism constitute the main land use systems in semi-arid drylands in Kenya. However, limited studies have investigated how land use and management practices and seasonality affect soil properties that alter C, N, and P biogeochemical cycling in African drylands systems. Thus, this study was conducted to determine effects of: (1) sedentary agropastoral land-use system (SAL), (2) semi-nomadic pastoral land-use system (SNL)), (3) pasture enclosures and (4) seasonality on selected soil chemical properties and total C, N, and P stoichiometry in a semi-arid landscape in Kenya. Land use, enclosures, and seasonality affected chemical properties of soils and C, N, and P stoichiometry. Generally, Na, K, Ca, Mg and cation exchange capacity were higher in the dry than wet period. Soil C:N ratios were less than 5, while N:P and C:P ratios were 5–56 and 16–177, respectively. However, ratios of C:N, N:P and C:P were significantly higher in SNL than SAL. The C:P and N:P ratios in both land use systems were highly correlated ( r 2 > 0.70). During the wet season, C:N ratios of soils were higher inside enclosures in both land uses. Higher soil N:P and C:P ratios were observed during dry compared to wet seasons. The N:P and C:P ratios of soils were higher inside and outside enclosures in SAL and SNL, respectively. Land use, enclosures and seasonality exhibited different effects on chemical properties of soils and C:N:P stoichiometry ratios. Perennial vegetation cover in enclosures has a great potential to enhance soil health necessary to support pastoral land-use systems in semi-arid African drylands.

An Integrated Eco-geospatial Approach for Assessment of Riparian Health in Upper Stretch of the Ganga, India - Ashutosh Kumar Mishra; Nihal Gujre; Shalini Dhyani (Anthropocene Science, 2024)

Assessment of Tree Density, Tree Cover, Species Diversity and Biomass in Semi-arid Human Dominated Landscape Using Large Area Inventory and Remote Sensing Data - C. Sudhakar Reddy; K. V. Satish (Anthropocene Science, 2024)

Alien-Plant Invasion in the Anthropocene - R. K. Kohli (Anthropocene Science, 2024)

From Safety Against Floods to Safety at Floods*: Theory of Urban Resilience to Flood Adaptation and Synergy with Mitigation - Ashish Kumar Srivastava; Avijit Sahay (Anthropocene Science, 2023)
The intensity and frequency of flood are continuously increasing due to climate change. Cities across the world are susceptible to flood causing devastating damages to infrastructure and human life. Almost every country has taking measures to mitigate climate change primarily. However, due to urgency posed by climate change driven flood risk requires more holistic approach focusing on both mitigation and adaptation measures and synergy between these measures. Theory of urban resilience to flood has proposed a paradigm shift in response to flood by cities. Ecological resilience such as living with flood, nature-based solution for flood adaptation, and coping with flood due to community learning and experiences are more effective measures than engineering resilience, such as dykes, flood wall, dam, etc. This paper analyses critically the relevance of this theory and importance of level of resilience of cities for protection at flood rather than flood resistance.

Achieving Land Degradation Neutrality Through Tea Plantation: Future Prospect for Combating Climate Change in the Northeast Himalayan Region of India - Kingshuk Modak; Gaurav Mishra; Saurav Saha; Ingudam Shakuntala; Rosa Francaviglia (Anthropocene Science, 2023)

Transformative Potential of Higher Education Institutions in Fostering Sustainable Development in India - Neha Goyal; Mamta Tripathy; Varsha Singh; Gyan Prakash Sharma (Anthropocene Science, 2023)

Understanding and Adapting Ocean Decade Action - Dhinakarasamy Inbakandan (Anthropocene Science, 2023)

Towards the Assessment of Ecosystem Health of Ecosystems in Asia and Promoting Nature-Based Solutions - N. Manika; Deepu Sivadas; Oindrila Basu; Shalini Dhyani (Anthropocene Science, 2023)

The Neglected Role of Intraspecific Variation in Plastic Pollution Research - Katy R. Nicastro; Laurent Seuront; Lorenzo Cozzolino; William Froneman; Gerardo I. Zardi (Anthropocene Science, 2023)

Building the Road to a Resilient Asia–Pacific: A New Dawn Begins for Women’s Leadership in Disaster Risk Reduction in Samoa - Saumya Singh; R. K. Mall (Anthropocene Science, 2023)

India’s Presidency of G20: A Unique Opportunity for Building Global Partnerships for Sustainable Development - Harikesh B. Singh (Anthropocene Science, 2023)

Untying the Knots of Traditional Ecological Knowledge: A Sustainable Roadway to Resource Management in Asia - Tanu Kumari (Anthropocene Science, 2023)

Understanding the Research Interlinkages Between Anthropocene, Millennium and Sustainable Development Goals: A Global Bibliometric Analysis - Nandini Garai; Ajishnu Roy; Kousik Pramanick (Anthropocene Science, 2023)

Comparative Assessment of Tree Carbon Sequestration Potential and Soil Carbon Dynamics of Major Plantation Crops and Homestead Agroforestry of Kerala, India - Usha Mina; Greeshma Geetha; Rashmita Sharma; Deepti Singh (Anthropocene Science, 2023)

Deforestation Drivers Across the Tropics and Their Impacts on Carbon Stocks and Ecosystem Services - Tobias Seydewitz; Prajal Pradhan; David M. Landholm; Juergen P. Kropp (Anthropocene Science, 2023)
Globally, deforestation produces anthropogenic greenhouse gas (GHG) emissions, contributing substantially to climate change. Forest cover changes also have large impacts on ecosystem services. Deforestation is the dominant type of land cover change in tropical regions, and this land cover change relates to distinct causes recognized as direct deforestation drivers. Understanding these drivers requires a significant effort. Further, GHG emissions due to deforestation are quantified only in terms of biomass removal, while linking emissions from soil organic carbon (SOC) loss to deforestation is lacking. A closer picture of associated ecosystem service changes due to deforestation is also needed. We analyze for 2001–2010: (1) the magnitudes of deforestation drivers, (2) the related carbon loss, and (3) the ecosystem service value change. On the global scale, agriculture (90.3%) is the primary deforestation driver, where grassland expansion contributed the most (37.5%). The deforestation drivers differ in magnitude and spatial distribution on the continental scale. The total carbon loss by biomass removal and SOC loss accounted for 8797 Mt C and 1185 Mt C, respectively. Furthermore, tropical deforestation caused the ESV loss of 408 billion Int.$ year $$^{-1}$$ - 1 , while the resulting land cover has the ESV of 345 billion Int.$ year $$^{-1}$$ - 1 . Our findings highlight that agriculture substantially contributes to global carbon loss and ecosystem service loss due to deforestation. The deforestation drivers differ in magnitude and distribution for different continents. Further, we highlight the danger of putting a monetary value on nature.

Securing Wild Edible Plants for Planetary Healthy Diet - Amit Kumar Bundela; Purushothaman Chirakkuzhyil Abhilash; Josep Peñuelas (Anthropocene Science, 2023)

Advocating Sustainable Use of Wild Species for Enhancing Food Security, Ecosystem Conservation and Planetary Resilience - Priya Priyadarshini; Amit Kumar Bundela (Anthropocene Science, 2023)

Composition, Relative Abundance, and Diversity of Medium and Large Mammals in Tirba Lake Awi Zone, Ethiopia - Binega Derebe; Yonas Derebe; Bahiru Gedamu (Anthropocene Science, 2023)

Sustainable Food System in Ghana: Role of Neglected and Underutilized Crop Species and Diversity - Bandanaa Joseph; Bissah Matilda Ntowa; Owusu Edmund Osei; Tetteh Rashied; Adu Amoah Richard; Kwateng Yaw; Aboagye Lawrence Misa; Nutsugah Stephen; Kotey Daniel Ashie (Anthropocene Science, 2023)

Nexus Between Urbanization, Industrialization, Natural Resources Rent, and Anthropogenic Carbon Emissions in South Asia: CS-ARDL Approach - Liton Chandra Voumik; Mahinur Begum Mimi; Asif Raihan (Anthropocene Science, 2023)

Mapping Peer-Reviewed Scientific Studies on Plant Trait–Service Linkages Across Ecosystems: A Bibliometric Analysis - Arkajyoti Shome; Shyam S. Phartyal; Pyarimohan Maharana; Anurag Verma (Anthropocene Science, 2023)

Climate Change and Biodiversity Synergies: A Scientometric Analysis in the Context of UNFCCC and CBD - Himangana Gupta; Neeraj Kumar Singh (Anthropocene Science, 2023)

Gas Flaring in Nigeria: A Multi-level Governance and Policy Coherence Analysis - Godwin O. Aigbe; Lindsay C. Stringer; Matthew Cotton (Anthropocene Science, 2023)
The unnecessary flaring of natural gas impacts public and environmental health, contributes to climate change and wastes fuel resources. Though reducing flaring is an emergent global environmental governance priority, progress has been slow. We assess gas flaring policy in the critical case of Nigeria through multi-level governance (MLG) structure. Our analysis assesses policy coherence (leading to progress in reaching shared goals) and divergence (creating tension and undermining progress) amongst sectors and institutional structures across the supranational, federal, state and local government scales. A combined dataset of documents, stakeholder interviews and expert surveys is analysed using Qualitative Document Analysis (QDA) and content analysis. We identify the principal actors involved, examine the extent of gas flaring awareness and policy coherence across multiple sectors/policy domains, and assess progress towards Nigeria’s national intended contribution and national policy on climate change mitigation. We find that policy coherence around gas flaring, including efforts towards climate change mitigation, has been slowed by political partisanship, poor governance, lack of regulatory compliance, and policy conflict between environmental protection and economic development priorities. Nigeria urgently requires inclusive involvement of stakeholder voices across multiple sectors and scales of local/regional government, the strengthening of federal institutions, a revaluation of economic aspirations through revenue diversification, and leadership that can temper the power of International Oil Companies (IOCs) to exploit the complexity of the MLG structure. These actions would help the government in improving environmental justice outcomes for flaring-affected communities.

Transforming the Agri-food Sector in India for Achieving the Sustainable Development Goals - Himanshu Pathak (Anthropocene Science, 2023)

Plant–Microbe Dynamics as a Nature-Based Solution for Sustainable Agriculture - Shobhit Raj Vimal; Jay Shankar Singh; Sheo Mohan Prasad (Anthropocene Science, 2023)

Coal-Fired Thermal Power Plants and Mercury Risks: Status and Impacts to Realize Minamata Convention Promises - Sunidhi Singh; Shalini Dhyani; Paras R. Pujari (Anthropocene Science, 2023)

Change in Structural Components Due to Seasonal Flooding Governs Provisioning Ecosystem Service Delivery and Livelihood Diversification: A Case Study from a Tropical Floodplain Wetland in Barak Valley Region of India - Priyanka Sarkar; Tapati Das; Raju Mandal; Dibyendu Adhikari (Anthropocene Science, 2022)

Comparing the Efforts, Evaluations, Perceptions, and Wishes of Citizens and Governments Regarding the MDGs and SDGs: A Case Study from Abuja, Nigeria - Yukako Inamura; Pankaj Kumar (Anthropocene Science, 2022)

Pathways for Sustainable Economic Benefits and Green Economies in Light of the State of World Forests 2022 - Deepu Sivadas (Anthropocene Science, 2022)

A Three-Tier Approach as a Next-Gen Sustainable Solution for Mitigation of Urban Air Pollution - Chetan Keswani; Tatiana Minkina; Svetlana Sushkova; Saglara Mandzhieva (Anthropocene Science, 2022)

Assessing Environmentally Effective Post-COVID Green Recovery Plans for Reducing Social and Economic Inequality - James R. Sokolnicki; Annabel L. Woodhatch; Richard Stafford (Anthropocene Science, 2022)
Given the current environmental crisis there have been multiple calls for a green recovery from COVID-19 which address environmental concerns and provide jobs in industries and communities economically damaged by the pandemic. Here, we holistically evaluate a range of recovery scenarios, evaluated on environmental and socio-economic equity metrics. Using a modified version of a Bayesian belief network, we show that economic stimuli across green sectors, including jobs in renewable energy, waste management, retrofitting of buildings, heat-pump installation and public transport can help economic growth, but will have limited environmental benefits. The inclusion of carbon taxes and ending fossil fuel subsidies, alongside investment in nature-based solutions and jobs in ecological conservation, can greatly increase the environmental gains as well as socio-economic equality. Additionally, jobs not associated with green industries, but with low carbon footprints, such as those in social care can further improve social equality with minimal negative environmental effects. However, in these latter scenarios involving taxation and ending fossil fuel subsidies, economic growth is reduced. We suggest a comprehensive green recovery and green new deal are needed, and we should reimagine economies, without the focus on economic growth.

Instructions for a Sustainable Anthropocene - S. Bastianoni; F. M. Pulselli; L. Coscieme; N. Marchettini (Anthropocene Science, 2022)

Advances in Ecosystem Services Valuation Studies in India: Learnings from a Systematic Review - Bhuvan Chopra; Y. S. C. Khuman; Shalini Dhyani (Anthropocene Science, 2022)

Ecology for Sustainable Development in the Anthropocene - Purushothaman Chirakkuzhyil Abhilash (Anthropocene Science, 2022)

Recarbonizing Global Soils for Sustainable Development - Rama Kant Dubey (Anthropocene Science, 2022)

Inside the Anthropo-Populo-Consumo-Capitalocene - Joachim H. Spangenberg (Anthropocene Science, 2022)

The COVID-19 Pandemic has Derailed the Progress of Sustainable Development Goals - Priya Priyadarshini (Anthropocene Science, 2022)

Nature-Based Nanocarrier System: An Eco-friendly Alternative for Improving Crop Resilience to Climate Changes - Estefânia Vangelie Ramos Campos; Anderson do Espirito Santo Pereira; Jhones Luiz de Oliveira; Gabriela Patricia Unigarro Villarreal; Leonardo Fernandes Fraceto (Anthropocene Science, 2022)

Climate Resilient Development Pathways in Global Drylands - Lindsay C. Stringer; Nicholas P. Simpson; E. Lisa F. Schipper; Siri H. Eriksen (Anthropocene Science, 2022)
The Intergovernmental Panel on Climate Change (IPCC) Working Group II Report on Adaptation, Impacts and Vulnerability identifies the urgent need to embark upon Climate Resilient Development Pathways. Climate Resilient Development acknowledges that adaptation needs to be undertaken together with mitigation and development, in joined-up, inclusive, just and equitable ways, across multiple arenas of engagement. In highly vulnerable systems with complex development contexts, such as drylands, where globally, warming is already exceeding that of humid areas, urgent action is vital, as the window of opportunity for Climate Resilient Development is rapidly closing. This paper considers challenges and opportunities in charting Climate Resilient Development Pathways in the world’s drylands. It highlights the importance of stakeholder engagement and partnership building to harness diverse knowledge sources, situating equity and justice concerns at the core of decision making and actions such as land restoration. It notes that while technological solutions offer potential to advance Climate Resilient Development, they need to be developed in an inclusive manner and used in ways that do not undermine Indigenous knowledge and local knowledge or exacerbate inequalities. Many of the challenges to Climate Resilient Development go beyond technology to include highly contextual differences in understanding, environment, institutions and access to finance. Adequate assessment of trade-offs in Climate Resilient Development actions in drylands remains vital to the framing of Climate Resilient Development Pathways for different groups. The paper concludes by identifying major urgent research gaps considering upscaling, stakeholder responsibilities and governance, the magnitude of investment that is necessary, and the need for appropriate monitoring, evaluation and learning.

Nexus Between Emission Reduction Factors and Anthropogenic Carbon Emissions in India - Asif Raihan; Almagul Tuspekova (Anthropocene Science, 2022)

Harnessing the Potentiality of Farm Landscape for Trees Based on Satellite Evaluation: A GIS Modeling Perspective - Firoz Ahmad; Nazimur Rahman Talukdar; Chandrashekhar M. Biradar; Shiv Kumar Dhyani; Javed Rizvi (Anthropocene Science, 2022)

Climate Extremes are Becoming More Frequent, Co-occurring, and Persistent in Europe - Prajal Pradhan; Tobias Seydewitz; Bin Zhou; Matthias K. B. Lüdeke; Juergen P. Kropp (Anthropocene Science, 2022)
With global warming, many climate extremes are becoming more frequent, often co-occurring, or repeatedly occurring in consecutive years. However, only limited studies have investigated these changes of climate extremes together. We study these changes in Europe for the last seven decades (1950–2019) based on 39 climate indices to identify climate extreme hotspots and coldspots. These indices belong to the four climate index groups: cold, heat, drought, and precipitation. Compared to the first half of the study period (1950–1984), most of our study locations faced heat extremes that are more frequent and occurring in consecutive years in the second half (1985–2019). However, the number of cold extremes has decreased in most locations. Simultaneously, some locations, mainly the Mediterranean region, faced an increase in droughts while others, e.g., parts of Eastern Europe and Northern Europe, experienced more intense precipitation. Two or more of these cold, heat, drought, and precipitation extremes have also co-occurred in a few locations of our study area in the same year. Our study highlights that climate extremes are becoming more frequent, co-occurrent, and persistent in Europe. These changes in climate extremes are associated with climate change. Therefore, we could infer that climate change mitigation is crucial for limiting these extremes.

The Ruling King of Bhutan and a Limnologist from USA Shared the Prestigious Blue Planet Prize 2022 - Pankaj Srivastava; M. Kiranmai Reddy (Anthropocene Science, 2022)

Short-Term Effects of Bamboo Plantation on Soil Carbon Fractions, Carbon and Nitrogen Stocks in Eastern Himalayas, India - Khikeya Semy; Gaurav Mishra; Rosa Francaviglia (Anthropocene Science, 2022)

Transition Pathways for Attaining Sustainability in Indian Agriculture by 2030 - Priya Priyadarshini; Amit Kumar Bundela; Krishna Kumar Pandey (Anthropocene Science, 2022)

Anthropocene Geochemical and Technological Signatures of an Experimental Landfill Bioreactor in the Central Valley of California - Gry H. Barfod; Reinhard Seiser; Ramin Yazdani; Li Wang; Charles E. Lesher; Bryan M. Jenkins; Peter Thy (Anthropocene Science, 2022)
The geochemical signatures of a 12-year-old experimental bioreactor at a California landfill are used to identify elemental concentrations and ratios that characterize the landfill and relate it to the age and state of technology of the deposited waste. The bioreactor was constructed and sealed with a synthetic liner during 2001–2002 and operated and monitored as an anaerobic digester to enhance methane production. In 2013, the bioreactor was sampled and trace element concentrations of the extracted fine fractions were determined. The concentrations normalized to a regional soil composition, reveal systematic peaks for transition metals, alkali metals, heavy metals, and various metalloids and non-metals. A group of potential solder elements (Cu, Zn, Cd, In, Sn, Pb, Bi, and Sb) shows moderate to strong co-variations and is largely attributed to household electronic components and other similar products, while elements that correlated well with rare-earth and other elements are related to the diluting effect of a soil component used as cover. Batteries show modest to little effects on the overall concentrations. Circulating fluids (recycled leachate) in the controlled reactor did not completely redistribute and homogenize the elemental signatures within the time frame of the bioreactor. It is concluded that the present experimental landfill defines an Anthropocene marker identifiable by building material (plaster), PVC plastic, and household electronic components (Pb–Sn solder). These marker elements and ratios are variably diluted by soil components identified by alkali metals, rare-earths, and high field-strength elements (Hf, Zr, Nb, and Ta).

The United Nations General Assembly Passes Historic Resolution to Beat Plastic Pollution - Amit Kumar Bundela; Krishna Kumar Pandey (Anthropocene Science, 2022)

Democracy and Sustainable Development - Dan Banik (Anthropocene Science, 2022)
The democratic discourse on climate change and sustainable development is becoming increasingly polarized. While some voters are pushing back against the movement to wean the world economy away from fossil fuels, others are questioning the huge costs that the transition to a green economy will impose and whether such attempts will have the required impact. This essay discusses the relationship between democracy and sustainable development by comparing the records of China and India in relation to the 2030 Agenda and the Sustainable Development Goals (SDGs). It argues that the politics of sustainable development has not received the attention it deserves. With a growing number of actors involved at various levels of society, the sustainable development narrative has often focused on a win–win narrative while glossing over areas where political agreement is more difficult to reach. While autocracies can achieve good results, democracy provides the best platform and guarantees for difficult negotiations and deliberations that are required for the achievement of sustainable development.

Analyzing Socio-Metabolic Vulnerability: Evidence from the Comoros Archipelago - Jean-Baptiste Bahers; Simron Singh; Mathieu Durand (Anthropocene Science, 2022)

Advancing Global Biodiversity Governance: Recommendations for Strengthening the Post-2020 Global Biodiversity Framework - Priya Priyadarshini; Amit Kumar Bundela; Alexandros Gasparatos; Lindsay C. Stringer; Shalini Dhyani; Rajarshi Dasgupta; Chintala Sudhakar Reddy; Himlal Baral; Roldan Muradian; Madhav Karki; Purushothaman Chirakkuzhyil Abhilash; Josep Peñuelas (Anthropocene Science, 2022)

Assessment of Socio-technical Constraints of Marine Fishers in the Utilisation of Marine Fishery Advisories in Southern Odisha, India - Harini Santhanam; Sudip Kumar Kundu (Anthropocene Science, 2022)

Suitability Assessment and Carbon Mitigation Potential of Plantations on India’s Railway Land - Rajiv Kumar Chaturvedi; Karun Jose; B. V. R. Shruthi; Karan Piyush Kariya; Amit Garg (Anthropocene Science, 2022)

Botanicals for Sustainable Management of Stored Food Grains: Pesticidal Efficacy, Mode of Action and Ecological Risk Assessment Using Computational Approaches - Bhanu Prakash; Prem Pratap Singh; Akshay Kumar; Vishal Gupta (Anthropocene Science, 2022)

Assessing the Realization of Global Land Restoration: A Meta-analysis - Sheikh Adil Edrisi; Priyanka Sarkar; Jaewon Son; Nagaraja Tejo Prakash; Himlal Baral (Anthropocene Science, 2022)

Valuing Ecosystem Services of Sacred Natural Sites in the Anthropocene: A Case Study of Varanasi, India - Rinku Singh; Amit Kumar Tiwari; Anil Sharma; Sanoj Kumar Patel; Gopal Shankar Singh (Anthropocene Science, 2022)

Is ‘Anthropocene’ a Suitable Chronostratigraphic Term? - Eugenio Luciano (Anthropocene Science, 2022)
Over the past two decades, the term ‘Anthropocene’ has ignited widespread academic and public interest. Since 2009, the term has been considered on stratigraphic grounds by the Anthropocene Working Group (AWG). The AWG has been championing a chronostratigraphic definition of the Anthropocene by advancing a proposal to formally recognize the unit as a post-Holocene epoch/series on the Geologic Time Scale and International Chronostratigraphic Chart. The proposal (i.e., the Anthropocene Hypothesis) has ignited debates among human, social, and natural scientists alike. One line of critique against the proposal concerns the chronostratigraphic suitability of the term ‘Anthropocene.’ This type of criticism holds that the term is inconsistent with the standard naming practices of the chronostratigraphic series; that it is inconsistent with other epochs of the Cenozoic era; that its etymology is faulty in several respects; and/or that its informal nature should be emphasized stylistically (e.g., with quotation marks or by writing the term with a lower case initial). The present contribution reviews this criticism and discusses it in the context of (chrono)stratigraphic classification and nomenclature to assess whether ‘Anthropocene’ is a suitable chronostratigraphic term. To do so, the analysis comments on and discusses guidelines, recommendations, and suggestions drafted by the International Stratigraphic Guide, which represents an international framework of reference for stratigraphic classification and nomenclature. Based on the underlying philosophy and recommendation of the Guide, there seem to be reasons to consider the ‘Anthropocene’ a suitable term in the context of chronostratigraphic nomenclature.

Restoring Riparian Ecosystems During the UN-Decade on Ecosystem Restoration: A Global Perspective - Mahesh Mohan; Ashly Chacko; Mutharimettak Rameshan; Velamparambil Gopalakrishnan Gopikrishna; Vatharamattathil Mohanan Kannan; Nalinakshan Geetha Vishnu; Sasi Arun Sasi; Kalathilparambil Rajappan Baiju (Anthropocene Science, 2022)

Ecosystem Health and Risk Assessments for High Conservation Value Mountain Ecosystems of South Asia: A Necessity to Guide Conservation Policies - Shalini Dhyani; Deepu Sivadas; Oindrila Basu; Madhav Karki (Anthropocene Science, 2022)

Food Security Challenges and Options in the Caribbean: Insights from a Scoping Review - Elham Mohammadi; Simron Jit Singh; Cameron McCordic; Jeremy Pittman (Anthropocene Science, 2022)